2014
DOI: 10.1159/000362809
|View full text |Cite
|
Sign up to set email alerts
|

Acne Smart Club: An Educational Program for Patients with Acne

Abstract: Objective: To evaluate adherence to therapy in acne patients using mobile phones and Short Message Service (SMS) to communicate. Methods: 160 patients were randomly assigned to two groups: the SMS group received 2 text messages twice a day for a period of 12 weeks; the control group did not receive any messages. Before and after 12 weeks, the following evaluations were performed in all patients: digital photographs, the Global Acne Grading System, the Dermatology Life Quality Index, the Cardiff Acne Disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Although our search included studies published since 1995, no eligible studies were identified before 2005, with most studies (12/15, 80%) published since 2010 (Table 1) [34-39,41-44,46,48]. Most studies were performed in the United States (in whole or in part; 11/15, 73%) [34,36-38,41,42,44-48].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Although our search included studies published since 1995, no eligible studies were identified before 2005, with most studies (12/15, 80%) published since 2010 (Table 1) [34-39,41-44,46,48]. Most studies were performed in the United States (in whole or in part; 11/15, 73%) [34,36-38,41,42,44-48].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were performed in the United States (in whole or in part; 11/15, 73%) [34,36-38,41,42,44-48]. Studies targeted eight different CHCs, including those of adolescents with acne (n=2) [34,39], asthma (n=1) [47], depression (n=1) [42], diabetes mellitus (n=4) [35,40,43,46], human immunodeficiency virus (n=2) [37,41], liver transplant (n=2) [44,45], sickle cell disease (n=2) [36,38], and systematic lupus erythematosus (n=1) [48]. Most studies were small in size (ie, ˂50 participants; 11/15, 73%) [34-37,42-48], and just over half (8/15, 53%) included samples of young adults (with a mean or median age ≥18 and ≤24 years old) [34,37,39,41-43,47,48].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations